A Dissenters’ View on AppleSnail Immunobiology - Rodriguez, Cristian; Vega, Israel A.; Castro-Vazquez, Alfredo (Frontiers in Immunology, 2022)
We stand as dissenters against the acceptance of scientific knowledge that has not been built on empirical data. With this in mind, this review synthesizes selected aspects of the immunobiology of gastropods and of apple snails (Ampullariidae) in particular, from morphological to molecular and “omics” studies. Our trip went through more than two centuries of history and was guided by an evo-devo hypothesis: that the gastropod immune system originally developed in the mesenchymal connective tissue of the reno-pericardial complex, and that in that tissue some cells differentiated into hematopoietically committed progenitor cells that integrate constitutive hemocyte aggregations in the reno-pericardial territory, whether concentrated in the pericardium or the kidney in a species-specific manner. However, some of them may be freed from those aggregations, circulate in the blood, and form distant contingent aggregations anywhere in the body, but always in response to intruders (i.e., pathogens or any other immune challenge). After that, we reviewed the incipient immunology of the Ampullariidae by critically revising the findings in Pomacea canaliculata and Marisa cornuarietis, the only ampullariid species that have been studied in this respect, and we attempted to identify the effectors and the processes in which they are involved. Particularly for P. canaliculata, which is by far the most studied species, we ask which hemocytes are involved, in which tissues or organs are integrated, and what cellular reactions to intruders this species has in common with other animals. Furthermore, we wondered what humoral factors could also integrate its internal defense system. Among the cellular defenses, we give an outstanding position to the generation of hemocyte nodules, which seems to be an important process for these snails, serving the isolation and elimination of intruders. Finally, we discuss hematopoiesis in apple snails. There have been contrasting views about some of these aspects, but we envision a hematopoietic system centered in the constitutive hemocyte islets in the ampullariid kidney.